PELATIHAN PENGEMBANGAN KOMPETENSI SISWA DALAM MERANCANG UI/UX MENGGUNAKAN FIGMA PADA SMK MUHAMMADIYAH 2 PEKANBARU - Syefrida Yulina; Satria Perdana Arifin; Yohana Dewi Lulu Widyasari (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
provide students with a basic understanding of user interface (UI) design and user experience (UX). The background to this activity is the importance of UI/UX skills in the increasingly developing digital world of work, especially for vocational school students who are prepared to go straight into industry. The methods used include providing theoretical material through presentations, demonstrations of the use of Figma tools, as well as direct practice by students. Design and development activities involve gradual teaching, starting from an introduction to basic UI/UX concepts, an introduction to the Figma interface, to the practice of making simple prototypes. Testing is carried out through evaluating students' work to improve the quality of their understanding and skills. The conclusion of this activity shows that students can understand and apply basic UI/UX concepts using Figma tools, and are able to produce creative and functional prototype designs. This program can improve students' competence in the field of digital design and prepare them for challenges in the world of work.